A novel platform using homobifunctional hydrazide for enrichment and isolation of urinary circulating RNAs - Bonhan Koo; Yunlim Kim; Yoon Ok Jang; Huifang Liu; Myoung Gyu Kim; Hyo Joo Lee; Myung Kyun Woo; Choung‐Soo Kim; Yong Shin (Wiley, 2023)
Abstract Changes in specific circulating RNA (circRNA) expressions can serve as diagnostic noninvasive biomarkers for prostate cancer (PCa). However, there are still unmet needs, such as unclear types and roles of circRNAs, PCa detection in benign prostatic hyperplasia (BPH) by unstandardized methods, and limitations of sample volume capacity and low circRNA concentrations. This study reports a simple and rapid circRNA enrichment and isolation technique named "HAZIS‐CirR" for the analysis of urinary circRNAs. The method utilizes homobifunctional hydrazides with amine‐modified zeolite and polyvinylidene fluoride (PVDF) syringe filtration for combining electrostatic and covalent coupling and size‐based filtration, and it offers instrument‐free isolation of circRNAs in 20 min without volume limitation, thermoregulation, and lysis. HAZIS‐CirR has high capture efficiency (82.03%-92.38%) and a 10‐fold more sensitive detection limit (20 fM) than before enrichment (200 fM). The clinical utility of HAZIS‐CirR is confirmed by analyzing circulating mRNAs and circulating miRNAs in 89 urine samples. Furthermore, three miRNA panels that differentiate PCa from BPH and control, PCa from control, and BPH from control, respectively, are established by comparing miRNA levels. HAZIS‐CirR will be used as an optimal and established method for the enrichment and isolation of circRNAs as diagnostic, prognostic, and predictive biomarkers in human cancers.